(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Present the clinical characteristics and traditional medicine types of patients with osteoporosis at Tue Tinh Hospital in 2024. Method: Analytical cross-sectional descriptive study. Overall sample size, collected 265 patients diagnosed with osteoporosis. Results: Osteoporosis patients are mainly female (90.2%), the group over 60 years old accounts for 68.7%, common accompanying diseases are sciatica, neck pain and knee osteoarthritis. The most common clinical symptoms are: back pain (80%), cramps (32.1%), bone pain (55.1%), 79.2% of patients are overweight. According with traditional medicine, the patient’s typs are: kidney deficient (24.9%), yang kidney deficient (12.9%), phlegm-dampness (12.9%) and yin kidney deficient (14.7%). Group of patients who had DEXA bone density testing results T-score < -3.5 are 21.5%. Conclusion: Osteoporosis is common in women over 60 years old. According to traditional medicine types, the most common physical condition at the time of admission is kidney deficient and phlegm-dampness constitution